Pengaruh Etika Profesi dan Independensi Terhadap Kinerja Auditor dengan Profesionalisme Sebagai Intervening dan Spiritual Quotient Sebagai Moderating - Ahmad Fauzan; Hardi Hardi; Meilda Wiguna (SYNERGY: Jurnal Bisnis dan Manajemen, 2026)
This study aims to examine and analyze the influence of Professional Ethics and Independence on Auditor Performance with Professionalism as an intervening variable and Spiritual Quotient (SQ). In this study, the author uses an associative approach, with primary data sources. The data collection technique used was distributing questionnaires to 101 auditors working at Public Accounting Firms in Pekanbaru City. The sampling technique used was saturated sampling. The data analysis techniques used in this study are outer model analysis, inner model analysis and hypothesis testing using Partial Least Square (PLS) software version 4. The results of this study indicate that 1) Professional Ethics has a significant effect on Auditor Performance, 2) Professional Ethics has a significant effect on Auditor Professionalism, 3) Independence has a significant effect on Auditor Performance, 4) Independence has a significant effect on Auditor Professionalism, 5) Professionalism has a positive and significant effect on Auditor Performance, 6) Professionalism mediates the relationship between Professional Ethics and Auditor Performance, 7) Professionalism mediates the relationship between Independence and Auditor Performance, 8) Spiritual Quotient (SQ) moderates the effect of Professional Ethics on Auditor Performance, 9) Spiritual Quotient (SQ) moderates the effect of Independence on Auditor Performance